2002
DOI: 10.1074/jbc.m112468200
|View full text |Cite
|
Sign up to set email alerts
|

Genes Essential to Sodium-dependent Bicarbonate Transport in Cyanobacteria

Abstract: The cyanobacterium Synechocystis sp. strain PCC 6803 possesses two CO 2 uptake systems and two HCO 3 ؊ transporters. We transformed a mutant impaired in CO 2 uptake and in cmpA-D encoding a HCO 3 ؊ transporter with a transposon inactivation library, and we recovered mutants unable to take up HCO 3 ؊ and grow in low CO 2 at pH 9.0. They are all tagged within slr1512 (designated sbtA). We show that SbtA-mediated transport is induced by low CO 2 , requires Na ؉ , and plays the major role in HCO 3 ؊ uptake in Syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
225
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(236 citation statements)
references
References 34 publications
9
225
1
1
Order By: Relevance
“…Hence, to our knowledge, Microcystis is the first example of a cyanobacterium in which bicA and sbtA are located on the same operon. The presence of a sodium/proton antiporter gene on the same operon strengthens the hypothesis (Shibata et al, 2002;Price et al, 2004) that bicarbonate transport by BicA and SbtA is sodium-dependent. The presence of an upstream LysR-type transcriptional regulator gene, ccmR2, makes it likely that transcription of the bicA-sbtAB-nhaS3 operon is strongly regulated and dependent on environmental conditions.…”
Section: Ccm Genes Of Microcystissupporting
confidence: 57%
See 2 more Smart Citations
“…Hence, to our knowledge, Microcystis is the first example of a cyanobacterium in which bicA and sbtA are located on the same operon. The presence of a sodium/proton antiporter gene on the same operon strengthens the hypothesis (Shibata et al, 2002;Price et al, 2004) that bicarbonate transport by BicA and SbtA is sodium-dependent. The presence of an upstream LysR-type transcriptional regulator gene, ccmR2, makes it likely that transcription of the bicA-sbtAB-nhaS3 operon is strongly regulated and dependent on environmental conditions.…”
Section: Ccm Genes Of Microcystissupporting
confidence: 57%
“…So far, five different C i uptake systems have been identified in cyanobacteria, two for CO 2 and three for bicarbonate (Omata et al, 1999;Shibata et al, 2002;Price et al, 2004;Price, 2011). These uptake systems have different properties (Price et al, 2004), and not all uptake systems are present in every cyanobacterium (Rae et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, while CO 2 can freely diffuse in and out of the cell, HCO 3 À is a membrane-impermeable molecule. Although bicarbonate transport proteins have been identified in mammalian cells (Sterling and Casey, 2002) and cyanobacteria (Shibata et al, 2002), no such transporters have been reported in E. coli. While the principal reactions consuming bicarbonate/CO 2 in E. coli do so in the form of bicarbonate (whose only source is the hydration of CO 2 ), the reactions producing bicarbonate/CO 2 do so in the form of CO 2 .…”
Section: Feasibility Of Glycerol Fermentation In E Coli Ismentioning
confidence: 99%
“…1998;Omata et al . 1999;Shibata et al . 2002) and two CO 2 uptake systems associated with the operation of specialized NAD(P)H dehydrogenase complexes [one low-CO 2 inducible, dependent on NdhD3/NdhF3/CupA(ChpY); one constitutive, dependent on NdhD4/NdhF4/CupB(ChpX)] (Sültemeyer et al .…”
Section: Introductionmentioning
confidence: 99%